INTERNALISASI NILAI-NILAI MODERASI BERAGAMA DALAM PEMBELAJARAN PAI DAN BUDI PEKERTI DI SMK SEMEN GRESIK - Ikhwan Rasmana Tarigan; Muhammad Farih (MIYAH : Jurnal Studi Islam, 2025)
This study aims (1) To find out how to internalize the values of religious moderation in learning Islamic Religious Education. (2) What are the supporting and inhibiting factors for the internalization of religious moderation values in Islamic Religious Education learning. (3) What are the implications of internalizing the values of religious moderation in learning Islamic Religious Education. The method used in this study is a descriptive qualitative research method with a type of field research located at Smk Semen Gresik. The subjects of this research include school principals, teachers and students. The data collection technique uses interview, observation and documentation methods. The results of this study show that (1) Internalization of religious moderation values in learning Islamic Religious Education at Smk Semen Gresik through the stages of planning, implementation, and evaluation. The internalization of the values of religious moderation can be done by methods: a) Teaching method, b) Exemplary method, c) Motivation method, d) Habituation method, e) Rule enforcement method. (2) Supporting factors: a) high commitment from the principal, teachers, staff, and other stakeholders. On the other hand, the availability of facilities and infrastructure to support the learning process. b) extracurricular activities. c) the competence of educators in campaigning for religious moderation. Meanwhile, the inhibiting factors are that students are not wise in sorting and choosing information, hoax news, and content on radicalism issues, as well as the lack of a collection of literacy reading materials. (3) The implications of internalizing the values of religious moderation include obedience to rules such as obeying school rules that apply at school. And respect for others such as being friendly with anyone and not underestimating others, being reverent with teachers, and not preceding teachers when walking, as well as familiarity with friends and teachers. Social concern.